Barriers to Effective Preoperative Handover Communication in the Neonatal Intensive Care Unit. (September 2014) - Lorinc, Amanda; Roberts, David; Slagle, Jason; Tice, Jamie; France, Daniel; Weinger, Matthew B.
We sought to better understand the preoperative neonatal intensive care unit to operating room (NICU-to-OR) handover process and to elicit barriers to effective handovers. We first conducted observations of NICU-to-OR handovers to ascertain current handover practices, including the participants involved, handover content, as well as barriers and facilitators of effective handovers. We then developed a survey tool to assess the generalizability of our findings to other NICUs across the country. The resulting pilot data highlight key areas for future research and potential interventions to improve the quality of NICU-to-OR care transitions.